The Effect of Share Offering Quantities, Age Company, Size of the Company and Value of Share Offer on Initial Return - Arinta Dewi (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2020)
Every company would want to expand the company, the capital market is an alternative. Shares are traded first on the primary market before traded on the secondary market. The purpose of this study was to determine the results of the study of the Stock Offer Quantity, Company Age, Company Size and the Value of the Stock Offer to the Initial Return. Back to the top Provide Stock Offer Feedback, Company Age, Company Size and Share Offer Value to the Initial Return. Sampling in this study using a purposive sampling method. The results of this test were carried out on 11 samples. This research was conducted on the Indonesia Stock Exchange (IDX), namely in the banking company that conducted a Public Offering (IPO) from 2012 to 2016. The results of research that refer to the Quantity of the Stock Offer are not related to initial returns, the age of the company changes to the initial returns, The size of the company affects the initial return, and the value of the stock offering affects the initial return. Simultaneously the Quantity of the Stock Offer, Company Age, Company Size, and the Value of the Shares Offering to the Initial Return.